Infinite spherical well as model of quantum carnot engine - Khazali Fahmi; Aditya Tri Oktaviana; Endah Kinarya Palupi (FoundAE, 2023)
The potential well is a simple example that generally used to present an understanding of quantum mechanics. In this article, we used infinite spherical well model to evaluate the thermodynamic processes in a quantum Carnot engine. The energy of the particles depended on the value of n and l lead to complex calculations. For simplicity we used the Ï†100 and Ï†200 quantum states to determine work and efficiency of a quantum Carnot machine. The results obtained show that efficiency depends on the value of Â which is the ratio of RC and RB.